Operação serenata de amor: mediação, dados abertos e accountability para cidadania digital - COSTA JÚNIOR, Luiz pereira da (2023)
The research analyzes the civic innovation project “Operação Serenata de Amor”, composed by the artificial intelligence Rosie and the website Jarbas. Using the following approaches as a methodological path: document analysis (DUARTE and BARROS, 2005) bibliographical research (ANDRADE, 2010; LAKATOS and MARCONI, 2005) and descriptive/exploratory method (GIL, 1999; BRAGA, 2007; SILVA and MENEZES, 2001) . It is intended to investigate the process of creation and operationalization of the tool under the Accountability bias, in the parameters of responsibility and responsiveness (KOPPELL, 2005). We understand that because it is an open source collaborative initiative, it can be seen from the perspective of convergence and participatory cultures (JENKINS, 2008; SHIRKY, 2011) and also from the platform (D'ANDREA, 2020) (VAN DIJCK, 2013). Its core activity, the detection of possible suspicious expenses that can be questioned by the citizen, consists of a process of mediation between human and non-human agents, considered radical by Grusin (2015). In this investigation, it is interesting to know which sociotechnical criteria are involved in this artificial intelligence anchored in algorithmization to solve a specific problem (REGATTIERI, 2018) and how the object contributes to digital citizenship, from the perspective of accountability.